163k views
4 votes
-2/3X + 4/3 = -10/3

solve each equation by first eliminating all fractions ​

1 Answer

3 votes

The solution of -2/3X + 4/3 = -10/3 by first eliminating all fractions is 7.0006

Solution:

We have been given an equation as follows:


-(2)/(3 x)+(4)/(3)=-(10)/(3)

And we have been asked to solve each equation by first eliminating all fractions.

The only way to solve this equation is by converting each of its components into decimals since it is stated in the question that we should not solve it in fraction form.

To do so we will individually convert the fractions to decimals and then substitute them back into the equation.

The 1st fraction in decimal form is:


-(2)/(3)=-0.6666

The 2nd fraction in decimal form is:


(4)/(3)=1.3333

And the 3rd fraction in decimal form is:


-(10)/(3)=-3.3333

So, now we substitute the decimals instead of the fractions in the given equation as follows:


\begin{array}{l}{-0.6666 x+1.3333=-3.3333} \\\\ {-0.6666 x=-3.3333-1.3333} \\\\ {x=-(4.6666)/(-0.6666)} \\\\ {x=7.0006}\end{array}

Therefore, the value of x in decimal from is 7.0006

User Rdbisme
by
6.1k points